GEN Z DALAM DUNIA PENDIDIKAN - Moh Ishak; Bagus Baydhowi; Moh Mahfud; Mas’odi Mas’odi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Generation Z, which consists of individuals born from 1997 to 2012, brings special characteristics to the world of education. Gen Z grew up in the technological era, is very familiar with technology, is able to multitask, and tends to look for learning experiences that are interactive and relevant to real life. To support their fast and independent learning style, Gen Z demands a more personal, flexible and technology-based approach. However, digital distractions, social media pressures, and the need for digital literacy skills must be overcome. This article discusses how the world of education can adapt to the needs of Gen Z. This can be done by implementing learning technology, creating appropriate curricula, and using a more inclusive and collaboration-based learning approach. By understanding the features and requirements of Gen Z, educational institutions have the ability to create learning environments that not only educate but also empower this generation to face future hardships.